Nadando a casa - Levy, Deborah, (Nuevos tiempos (Madrid, Spain), 2015)
A mysterious woman who suffers from mental illness suddenly appears at a vacation villa where two families are staying and her interactions with them reveal secret details about their past and tensions within their relationships with each other.